Efeitos da salinidade, luminosidade e alimentação na larvicultura do camarão-da-amazônia, Macrobrachium amazonicum - Araújo, Mariana Cutolo de [UNESP] (2005)
The present thesis studied Macrobrachium amazonicum larvae for determining: 1) the minimal salinity required for the survival and development of feed deprived larvae; 2) the best light intensity suitable for larval development; 3) the digestive tract content (Artemia nauplii and/or inert food) and the larval stage at the beginning of exogenous food ingestion; and 4) the effect of feeding regimes on the development, digestive tract content, survival, productivity and growth. The results showed that these larvae do not survive in freshwater, but the development can be completed in low salinity (1‰). Mean light intensity of 7.8±2.5 μmol.s-1.m-2 (about 390±125 lux) improves M. amazonicum larval development, productivity and weight gain. Moreover, larvae at Zoea II stage start feeding on Artemia nauplii and this live food is required until zoea IV. Zoea III larvae prefer Artemia nauplii, but accept inert food when it is the only available food. Total substitution of inert diet in place of Artemia nauplii from zoea V stage does not affect M. amazonicum larval development